Impact of Check It: A Novel Community-Based Chlamydia Screening and Expedited Treatment Program for Young Black Men. Issue 1 (January 2022) - Stoecker, Charles; Shao, Yixue; Schmidt, Norine; Martin, David H.; Kissinger, Patricia J.
Abstract : Objectives: This study aimed to estimate the impact of the Check It program, a novel community-based chlamydia seek, test, and treat program for young Black men who have sex with women, on test positivity rates for chlamydia in young Black women. Methods: We used a synthetic control model to compare chlamydia test positivity rates in Orleans Parish (intervention site) with other similar parishes (control sites) in Louisiana. We estimated a model that used all other parishes as potential contributors to a synthetic control for Louisiana as well as a sample limited to the 40 parishes in Louisiana with the largest Black populations. Results: The Check It program was associated with a 1.69-percentage-point decline in chlamydia positivity in the first full year of operation and a 2.44-percentage-point decline in chlamydia positivity in the second full year of operation compared with control sites with the largest Black populations ( P = 0.05). Results were similar when the treatment site was compared with all other sites in Louisiana. Conclusions: The Check It program was associated with a significant decline in chlamydia testing positivity rates among women in Orleans Parish compared with control sites. Screening of young Black men who have sex with women can decrease rates in women living in the same community. Future recommendations for chlamydia screening of young men should be considered. Abstract : Check It, a novel community-based screening and expedited treatment program for young, Black men is shown to have impacts on chlamydia positivity rates among young, Black women.Supplemental digital content is available in the text.